Hubungan Antara Intensitas Menonton Tayangan Sinetron Kekerasan di Televisi dan Pola Komunikasi Keluarga dengan Tingkat Agresivitas oleh Anak - Pungkas Dwitanto; Tandiyo Pradekso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
This study aims to determine the relationship between the intensity of watching violent soap operas on television and family communication patterns with the level of aggressiveness by children. This research uses explanatory quantitative method. The data collection technique used is non-probability sampling with a sample of 50 respondents. The theory used in this research is social learning and relationship schemes in the family. Hypothesis testing using Kendall's Tau_b analysis and Chi-Square Tests. The results of the hypothesis test show that the significance value for the variable intensity of watching violent soap operas on television is 0.278, which means that there is a relationship between the intensity of watching violent soap operas on television (X1) and the level of aggressiveness by children (Y). Meanwhile, the results of the hypothesis test for the family communication pattern variable show that the significance value is 0.000, which means that there is a relationship between the parent's communication pattern (X2) and the child's level of aggressiveness (Y).